Waste Bank Management in Improving the Community Economy in Sokoyoso Village, Kajen District, Pekalongan Regency - Nofita Apriliani Putri; Hendry Hermawan Adinugraha; Beguin Sophie; Vandenhove Sophie (Pengabdian: Jurnal Abdimas, 2023)
Background. Large amount of plastic waste scattered on the side of the road and the village hall building. The purpose of this activity is to provide direction and information on managing waste banks to improve the welfare of the surrounding community, changing the mindset of the importance of protecting the environment and having a caring attitude towards natural resources that are owned to support the economy of the surrounding community, from this activity it can be concluded that bank management waste can improve the economy of the people in Sokoyoso Village, Kajen District, Pekalongan Regency. Purpose. The purpose of this activity is to provide direction and information on the management of waste banks to improve the welfare of the surrounding community, change the mindset of the importance of protecting the environment, and have a caring attitude towards the natural resources owned to support the economy of the surrounding community, from this activity it can be concluded that bank management waste can improve the economy of the community in sokoyoso Village, District.   Method. The collected waste will then be sold to collectors. Waste bank management can help reduce environmental pollution caused by humans, besides that waste bank management can help village income. Results. One of the problems that occur in Sokoyoso Village is the amount of plastic waste scattered on the roadside and the village hall building. Conclusion. The waste bank is one of the waste management that has been collected and sorted. The results of waste sorting aim that waste can be easily recycled according to its type, there are three types of waste in the waste bank management, namely organic waste, inorganic waste, and B3 waste. Garbage that has been collected will then be sold to collectors. Waste bank management can help reduce environmental pollution caused by humans, besides that waste bank management can help village income.